Golden letters : writing traditions of Indonesia = Surat emas: budaya tulis di Indonesia - Gallop, Annabel Teh; Arps, Ben (London : British Library, 1991)
Catalog of travelling photographic exhibition of royal Indonesian letters and manuscripts from British collections
Half title: Departemen Pariwisata, Pos, dan Telekomunikasi, Republik Indonesia mempersembahkan pameran surat emas raja-raja Nusantara dari koleksi Inggris
Includes bibliography (pages 148-152) and index
Keywords: Manuscripts -- Great Britain; Manuscripts -- Indonesia -- Union lists; Union catalogs -- Great Britain